2023
DOI: 10.1038/s41598-023-33142-x
|View full text |Cite
|
Sign up to set email alerts
|

Textural properties and adsorption behavior of Zn–Mg–Al layered double hydroxide upon crystal violet dye removal as a low cost, effective, and recyclable adsorbent

Abstract: The preparation of adsorbents plays a vital role in the adsorption method. In particular, many adsorbents with high specific surface areas and unique shapes are essential for the adsorption strategy. A Zn–Mg–Al/layer double hydroxide (LDH) was designed in this study using a simple co-precipitation process. Adsorbent based on Zn–Mg–Al/LDH was used to remove crystal violet (CV) from the wastewater. The impacts of the initial dye concentration, pH, and temperature on CV adsorption performance were systematically … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 99 publications
0
8
0
Order By: Relevance
“…Figure 1 displays the X-ray diffraction patterns of LAC before and after FLX adsorption, LAC-FLX. The peaks at 11.42°, 23.41°, 34.49°, 38.99°, 46.60°, 60.09°, 61.2°, and 65.13° correspond to LDH peaks of (003), (006), (012), (015), (018), (110), (113), and (116) 35 . The AC material exhibited peaks at 26.41° and 63.8°, which are associated with the (002) and (221) indices 36 .…”
Section: Resultsmentioning
confidence: 97%
“…Figure 1 displays the X-ray diffraction patterns of LAC before and after FLX adsorption, LAC-FLX. The peaks at 11.42°, 23.41°, 34.49°, 38.99°, 46.60°, 60.09°, 61.2°, and 65.13° correspond to LDH peaks of (003), (006), (012), (015), (018), (110), (113), and (116) 35 . The AC material exhibited peaks at 26.41° and 63.8°, which are associated with the (002) and (221) indices 36 .…”
Section: Resultsmentioning
confidence: 97%
“…The results showed that the R L values of PHT, PHB, and LTG were all distributed on a scale of 0 to 1, suggesting that a favorable process was present in the adsorption of PHT, PHB and LTG on MIPMs. 42 …”
Section: Resultsmentioning
confidence: 99%
“…The melting points of the samples were determined using the Electrothermal 9200 device and have not been modified. 1 H and 13 CNMR spectra of the products were taken using the Varian INOVA 500 MHz device. The FTIR spectrum of the samples was obtained using KBr tablets and the PerkinElmer GX FTIR device.…”
Section: ■ Experimentalmentioning
confidence: 99%
“…LDHs can be used as an attractive base in various applications, such as medical, pharmaceutical, sensors, and drug delivery. As a result, they have attracted a lot of attention. LDHs have a layered structure, which is also called hydrotalcite; it consists of divalent and trivalent cations, whose general formula is [Me 2+ (1 – x ) Me 3+ x (OH) 2 ] x +(An – ) x / n n •H 2 O. , It is possible to change cations and anions, which may affect the properties of the layers. Today, layered double hydroxides are excellent supports for various catalysts due to the numerous hydroxide groups on their surface. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation